VALIDATION OF ANTIBACTERIAL CLAIMS OF SOME HERBAL MEDICINAL PRODUCTS SOLD IN OTUKPO, BENUE STATE. (FUDMA JOURNAL OF SCIENCES, 2023)
The study is aimed at validating antibacterial claims of some herbal products sold in Otukpo, Benue State. The test organisms include: Staphylococcus aureus, Salmonella typhi, Escherichia coli, and Proteus vulgaris, which were obtained from Medical Laboratory unit of General Hospital Otukpo and were confirmed by sub-culturing on appropriate selective media and the use of biochemical tests in the Microbiology Laboratory, Department of Science Laboratory, Benue State Polytechnic, Ugbokolo. Ciprofloxacin was used as a positive and negative control. The degree of susceptibility of the test isolates to each herbal product was determined by measuring the diameter of the zones of inhibition.  Product Code I had the highest zone of inhibition of 36 mm against Escherichia coli, followed by Product Code F with zone of inhibition of 32 mm, while the least sensitive against Escherichia coli was Product Code D with zone of inhibition of 17 mm; all the herbal products where resistant to Staphylococcus aureus. Against Escherichia coli, the MIC and MBC values for Product Code F were 75 mg/ml and 100 mg/ml, respectively; while for Salmonella typhi, the MIC and MBC values for Product Code G were 28 mg/ml and 70 mg/ml, respectively. The overall result showed that most of the antibacterial claims by the herbal producers were not true as validated in this present work
Keywords: Validation, Bacterial isolates, Antibacterial, Claims and Medicinal products